Health-sickness process: student leaders’ conceptions in the health area - Reis, Alessandra Martins dos; Soares, Cássia Baldini; Campos, Célia Maria Sivalli (Saúde e Sociedade, 2010)
The goal of this paper was to analyze health-sickness conceptions of student leaders in the health area. Data were collected by means of individual interviews with 15 students who take part in regional committees for students' movements in the health area, and two members of the National Students Union. The most emphasized health-sickness conception among the student leaders was the multi-causal one, mostly represented by factors related to consumption. Also, perceptions centered on the individual, on subjectivity and idealistic conceptions stood out. Few students took into consideration, in an organized way, the category of social reproduction as determining the health-sickness process. We can conclude that in the health area, students tend to reproduce concepts based on the functionalist conception of health-sickness, which takes as subject the individual "in a state of risk" concerning the development of some pathology, and suggests that the individual is responsible for the maintenance of or improvement in his/her health conditions, or even for the fight against the disease. Acting as a student leader does not seem to result in criticism against the concepts that are mainly studied in university curriculums in the health area.